Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Terhadap Motivasi Belajar Siswa Mata Pelajaran Ekonomi Kelas XI MA Sunan Kalijogo Mojo Kediri - Faisal Maulana Putra; Jani Jani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research was motivated by a lack of student participation and boredom with the monotonous learning system so that students did not understand abstract and complex economic concepts. From these problems it can be seen that the cause is a lack of motivation to learn. So it is necessary to develop a learning model, one of which is the TGT (Teams Games Tournament) cooperative learning model using TTS. The aims of this research are (1) to determine the effect of the TGT learning model on students' learning motivation in economics subjects in Class XI MA Sunan Kalijogo Mojo Kediri; (2) To find out how much influence the TGT learning model has on the motivation to learn economics for class XI MA Sunan Kalijogo Mojo Kediri. The research approach used is quantitative, associative type. Data collection uses questionnaires and documentation. Data analysis and hypothesis testing using simple linear regression using SPSS. The research results show that (1) Based on the hypothesis test, the results obtained are sig. 0.000 < 0.05, it can be said that there is a positive and significant influence between the influence of the TGT learning model on students' economic learning motivation; (2) Based on the hypothesis test, a value (R) of 0.652 was obtained, which indicates a strong relationship between the two variables. Meanwhile, the R Square values ​​of 42.5% and 57.5% are influenced by other factors that have not been studied.